The function of a novel immunophenotype candidate molecule PD-1 in chronic lymphocytic leukemia. Issue 10 (3rd October 2015) - Grzywnowicz, Maciej; Karabon, Lidia; Karczmarczyk, Agnieszka; Zajac, Malgorzata; Skorka, Katarzyna; Zaleska, Joanna; Wlasiuk, Paulina; Chocholska, Sylwia; Tomczak, Waldemar; Bojarska-Junak, Agnieszka; Dmoszynska, Anna; Frydecka, Irena; et al.
Abstract : Programmed death-1 (PD-1) is a negative receptor expressed on lymphocytes including malignant B cells in chronic lymphocytic leukemia (CLL). In this work, we found that patients with CLL had a higher expression of PD-1 transcript ( PDCD1 ) than healthy volunteers ( p < 0.0001). PDCD1 expression was comparable between CLL cells from accumulation (peripheral blood) and proliferation (bone marrow) disease compartments. In blood samples of patients with mutated IGHV genes PDCD1 expression was higher than with unmutated IGHV ( p = 0.0299). We demonstrated that phosphorylation of SYK and LYN, key B-cell receptor signaling kinases, was independent of PD-1 expression in patients with CLL, while ZAP-70 phosphorylation in negative tyrosine residue 292 showed strong inverse correlation ( r = − 0.8, p = 0.0019). No associations between five single nucleotide polymorphisms of PDCD1, their expressions and susceptibility to CLL were found. In conclusion, PD-1 might be an independent, universal marker of CLL cells and a part of their activated phenotype, and subsequently might modulate the function of ZAP-70.